Efeitos do estresse neonatal sobre comportamentos relacionados a depressão em ratos wistar: influência do sexo e da idade - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Exposure to stressful early life events seems to interfere with brain development and the ability to cope with new environmental challenges in adolescence and adulthood. The development and plasticity of the hypothalamic-pituitary-adrenal axis (HPA) have also been proposed because it is environmentally dependent and maternal care. In addition, neonatal interventions increase the vulnerability of individuals to stress-related illnesses, such as depression. The present study investigated the effects of two models of neonatal stress, handling of 15 minutes/day and maternal separation of 3 hours/day between postnatal days 2 to 10, on depression-like behaviors in adolescence and adult life of Wistar males and females rats. The consequences of exposure to neonatal stress were assessed through changes in body mass, mass of the thymus and adrenal glands, and depression-like behaviors were evaluated using behavioral forced swimming test and sucrose preference. Our results showed that both neonatal stress protocols did not cause changes in body mass in adolescence and adulthood. A gender difference was observed only in adulthood, since control males, neonatal handling and maternal separation had higher body mass than the females of the respective groups. In relation to the mass of the thymus and adrenal glands in adolescence, it was only verified that the females had a higher relative mass of these organs when compared to males. In adulthood, maternal separation females showed involution of the thymus compared to females neonatal handling, while, they presented adrenal hypertrophy compared to females control and separation. The forced swimming test showed that maternal separation increased the immobility time of males and females compared to control and neonatal handling groups in adolescence and adulthood, as well as decreased swimming behavior in adult life. In the preference test for the sucrose solution, there was no difference in the preference for sucrose among the experimental groups in adolescence. While in adult life, males handling and separation, as well as control females showed a higher preference for sucrose compared to control males. In conclusion, exposure to adverse events early in life seems to contribute to the onset of depression. In addition, studies that evaluate the consequences of neonatal stress at different moments of life and the possible influences of sex are extremely important for the characterization and development of new treatment methods for depression.
Keywords: Separação materna; Manuseio neonatal; Adolescentes; Adultos; Machos; Fêmeas; Maternal separation; Neonatal handling; Adolescents; Adults; Males; Females; CIENCIAS DA SAUDE